UJI KEEFEKTIFAN CENDAWAN LECANICILLIUM MUSCARIUM DALAM MENGHAMBAT PERTUMBUHAN CENDAWAN PATOGEN TULAR TANAH (FUSARIUM OXYSPORUM, RHIZOCTONIA SOLANI, SCLEROTIUM ROLFSII) SECARA IN VITRO - CAHYADI, ABDURRAZAK (Universitas Negeri Surabaya, 2013)
One of the obstacles to the improvement and stabilization of crop production in Indonesia is soil borne disease pathogens that cause severe damage to agricultural crops in general and reduce both the quantity and quality of production. Three types of soil borne fungal pathogens commonly found in plants are F. oxysporum, R. solani and S. rolfsii, which resulted in the emergence of the fungus to soil borne diseases in crops such as corn, soybeans, potatoes, tomatoes, beans, cabbage, cucumber, cotton, and peanuts. This study aimed to describe the effectiveness of inhibiting fungus L. muscarium to inhibit the growth of F. oxysporum, R. solani and S. rolfsii in vitro. The experiment was conducted at the Laboratory of Microbiology, University of Surabaya C9 Building in October to December 2012. This study used the technique of exploratory observations made by growing the fungus in PSA medium for 5 days and then calculate the rate of growth of each fungus and calculate the inhibition of the fungus L. muscarium the three types of fungal pathogens. The results obtained were analyzed using descriptive quantitative analysis. From the results of this study concluded that the fungus L. muscarium has the effectiveness of different inhibitors on the three types of fungus pathogen (F. oxysporum, R. solani and S. rolfsii). The growth rate of each fungus did not show any difference. The fungus L. muscarium have rates similar maximal inhibitory effectiveness against fungus F. oxysporum and fungus R. solani by 66.31% and has a mean minimal inhibitory effectiveness against fungus S. rolfsii by 58.69%.